NEONATAL OUTCOMES IN POSTPARUM PSYCHOSIS. (September 2021) - Hazelgrove, K.; Biaggi, A.; Waites, F.; Conroy, S.; Osborne, S.; Pawlby, S.; Pariante, C.M.; Dazzan, P.
Abstract : Background: We aimed to examine neonatal behaviour and cortisol reactivity in neonates born to women at risk of postpartum psychosis (AR) who had a psychiatric relapse within 4 weeks post-delivery (AR-unwell), compared with neonates of women at risk who stayed well (AR-well) and those born to healthy women (HC). Methods: We assessed neonatal behaviour using the Neonatal Behavioral Assessment Scale (NBAS), performed on 105 neonates (AR-unwell=17; AR-well=27; HC=61). Neonatal cortisol was measured pre-, immediately post- and 30-minutes post-NBAS. Results: Neonates born to AR women did not differ from those born to HCs in behaviour or cortisol reactivity. There was also no difference in behaviour between neonates born to AR-unwell women and those born to AR-well women. However, neonates born to AR-unwell women had significantly lower pre-NBAS cortisol compared with neonates of AR-well women ( t (38) =2.3, p =.02). Neonates of AR-unwell women also had a greater increase in cortisol from pre- to post-NBAS, though the difference did not reach statistical significance ( p =.12), and a greater increase from pre- to 30 minutes post-NBAS ( t (32) =2.7, p =.01). Conclusion: Maternal postpartum symptoms appear to disrupt the stress response of neonates whose mothers are at risk of postpartum psychosis.